Expression of the Mucosal Homing Receptor α(4)β(7) Correlates with the Ability of CD8(+) Memory T Cells To Clear Rotavirus Infection - Rosé, Jason R. (American Society for Microbiology, 1998)
The integrin α(4)β(7) plays an important role in lymphocyte homing to mucosal lymphoid tissues and has been shown to define a subpopulation of memory T cells capable of homing to intestinal sites. Here we have used a well-characterized intestinal virus, murine rotavirus, to investigate whether memory/effector function for an intestinal pathogen is associated with α(4)β(7) expression. α(4)β(7)(hi) memory phenotype (CD44(hi)), α(4)β(7)(−) memory phenotype, and presumptively naive (CD44(lo)) CD8(+) T lymphocytes from rotavirus-infected mice were sorted and transferred into Rag-2 (T- and B-cell-deficient) recipients that were chronically infected with murine rotavirus. α(4)β(7)(hi) memory phenotype CD8(+) cells were highly efficient at clearing rotavirus infection, α(4)β(7)(−) memory cells were inefficient or ineffective, depending on the cell numbers transferred, and CD44(lo) cells were completely unable to clear chronic rotavirus infection. These data demonstrate that functional memory for rotavirus resides primarily in memory phenotype cells that display the mucosal homing receptor α(4)β(7).